Pengaruh pengiklanan tunjangan terhadap imej korporat mengikut tanggapan pengguna - Iskandar Abdullah; Chong, Yee Lee (Penerbit Universiti Kebangsaan Malaysia, 2001)
This research sought to understand how consumers evaluate advocacy advertising and thereon help to understand consumer perceptions of corporate image. The exploratory method was first conducted to understand how consumers associate advocacy advertising with the advertiser's image. This was followed by a detailed study of consumer perception of such advertising, was followed by a detailed study of consumer perception of such advertising, using the confirmatory method. This research found that the advertising, using the confirmatory method. This research found that the advertisement's attractiveness, followed by its trustworthiness and the message value congruency can influence consumers' perception on the advertiser's image. This was followed by a detailed study of consumer perception of such advertising, using the confirmatory method. This research found that the advertisement's attractiveness, followed by its trustworthiness and the message value congruency can influence consumers' perception on the advertiser's corporate image. Besides this, consumers were found to place less importance on the advertiser's expertise. Moreover, the advertiser and consumer's involvement in the issues they championed only passively influenced consumers' perceptions. We urge future researchers to explore and expand the scales discussed, as well as consider whether they will create a similar impact on commercial and non-commercial messages. Futhermore, how will the level of consumer assurance towards a certain product advertised, influence consumers' perception towards the advertiser's image?